XTR-Kurosawa-Desmedt Scheme (Communications in Mathematical Research, 2021)
This paper proposes an XTR version of the Kurosawa-Desmedt scheme. Our scheme is secure against adaptive chosen-ciphertext attack under the XTR version of the Decisional Diffie-Hellman assumption in the standard model. Comparing efficiency between the Kurosawa-Desmedt scheme and the proposed XTR-Kurosawa-Desmedt scheme, we find that the proposed scheme is more efficient than the Kurosawa-Desmedt scheme both in communication and computation without compromising security.
Keywords: XTR; Kurosawa-Desmedt scheme; adaptive chosen-ciphertext security; XTR-DDH assumption.